FINITE ELEMENT IMPLEMENTATION OF GEOMETRICALLY NONLINEAR CONTACT - Ondřej Faltus; Martin Horák (Acta Polytechnica CTU Proceedings)
The OOFEM finite element software has been recently updated to include contact algorithms for small strain applications. In this work, we attempt to extend the contact algorithms to large strain problems. Reviewing the current code and comparing it with approaches encountered in literature, we arrive at a specific algorithmic solution and integrate it into the current code base. The current code is explained, the necessary extensions are derived and documented, and the algorithmic changes are described. Tests confirm the functionality and quadratic rate of convergence of the proposed implementation.